High strain rate behaviour of nano-quasicrystalline Al93Fe3Cr2Ti2 alloy and composites - Pedrazzini, Stella; Galano, Marina L.; Audebert, Fernando E.; Siegkas, Petros; Gerlach, Robert; Tagarielli, Vito L.; Smith, George D.W. (My University, 2019)
We demonstrate the outstanding dynamic strength of nano-quasicrystalline Al93Fe3Cr2Ti2 at.% alloy and composites. Unlike most crystalline Al alloys, this alloy exhibits substantial strain rate sensitivity and retains ductility at high strain rates. This opens new pathways for use in safety-critical materials requiring impact resistance.
Keywords: Aluminium alloys; Dynamic testing; Hopkinson bar; Metal matrix composites; Quasicrystals